The need to use of intensification polices and inner city growth capacities in Tabriz / Mojtaba valibeigia and Ali Akbar taghipour - valibeigia, Mojtaba; taghipour, Ali Akbar (2012)
The optimal use of land is an important subject, due to the fast growth and unplanned urbanization of regions, in order to protect lands in fringe cites. This phenomenon is enumerated of evident characteristics in Iranian metropolitans the same as in other developing countries. Even though urban density in Tabriz is low, but a comparison with City net density or housing density shows a major part of inner city boundary spaces are useless. Many of the city's textures suffer from unfavorable spaces and low housing density. This research investigated sprawl expansion in Tabriz by available statistics and comparative - analysis method. Finding of Research shows that many parts of sprawl growth occur around the outer city because of inaccurate use of available lands. Thus this city do not need urban lands for fringe development until the next 15 years with accurate plans and adoption of a logical densification policy. Also intensification policies should be considered in Tabriz and actions in this field must be continuous and gradual actions.